Comparative Investigation on the Influence of Fouling and Scaling on the Membrane Filtration of Waste Water - Verhülsdonk, Marcus; Glas, Karl (BrewingScience, 2012)
Wastewater treatment should be viewed as one element of a holistic system targeted on the sustainable use of water. Recycling and the multiple utilization of not only water but also of the substances contained increasingly become an essential necessity. The application of a modular wastewater recycling was investigated for the treatment of anaerobic wastewater to process water. After the pretreatment, ultrafiltration and reverse osmosis are necessary to meet drinking water quality. The goal of this study is the stable operation of the membrane plants. In order to study the feasibility of the membranes, chemical and technical parameters as well as biofilm detection were observed during operation. During the operation period, biofilm development had no significant effect on the membrane performance. Scaling was the central issue problem. A calculation of the scaling potential showed that phosphate and carbonate salts tend to deposit on the membrane surface of the reverse osmosis. Based on the calculation of the scaling potential, a test was carried out with additional acid dosage to increase the solubility of salts. Within this test, a constant operation of the reverse osmosis without significant reduction in permeability was achieved. After 80 days of successful operation, the membranes were removed and analyzed by SEM/EDX to determine the scaling on the membrane surface.